2022
DOI: 10.1590/0004-282x-anp-2020-0591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebral hemodynamics by transcranial Doppler ultrasonography and its correlation with intracranial pressure in an animal model of intracranial hypertension

Abstract: Background: Transcranial Doppler has been tested in the evaluation of cerebral hemodynamics as a non-invasive assessment of intracranial pressure (ICP), but there is controversy in the literature about its actual benefit and usefulness in this situation. Objective: To investigate cerebral blood flow assessed by Doppler technique and correlate with the variations of the ICP in the acute phase of intracranial hypertension in an animal model. Methods: An experimental animal model of intracranial hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…ONSUS was performed in two opportunities with an average of 10 minutes of interval. The first measure at sedation induction with xylazine and ketamine, the second immediately after endotracheal intubation and administration of propofol or thiopental in concentrations adjusted for animals' weight in order to produce deep sedation 4 .…”
Section: Study Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…ONSUS was performed in two opportunities with an average of 10 minutes of interval. The first measure at sedation induction with xylazine and ketamine, the second immediately after endotracheal intubation and administration of propofol or thiopental in concentrations adjusted for animals' weight in order to produce deep sedation 4 .…”
Section: Study Animalsmentioning
confidence: 99%
“…These devices are invasive and can cause complications, including infections and bleeding. However, estimation and monitoring of ICP is feasible by means of noninvasive techniques [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters of transcranial Doppler (TCD) ultrasound, such as cerebral blood flow velocity (CBV), pulsatility index, and the ability to measure the diameter of the optic nerve sheath (discussed in a later section), have been studied as noninvasive biomarkers of ICP [84][85][86]. Although several early studies and a few recent studies have shown a strong correlation between TCD and ICP [87], a number of studies have shown varying correlations between TCD-determined ICP and invasively obtained ICP or have failed to show a correlation [84,[88][89][90][91].…”
Section: Transcranial Doppler Ultrasoundmentioning
confidence: 99%
“…Regarding the animals used for modeling ICH, the following different species were used: Mice or rats (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), pigs (34)(35)(36)(37)(38)(39)(40), dogs (41)(42)(43), monkeys (44), sheep (45), cats (46) and rabbits (47,48). The majority of studies (63%) utilized rats, whereas the model most used is autologous blood intracranial injection (51%).…”
Section: Modelsmentioning
confidence: 99%
“…Studies for ultrasound assessment of the optic nerve sheath diameter ( 34 , 94 ) and transcranial Doppler pulsatility index ( 35 ) have taken advantage of this method because of sudden IHT development. Thus, the balloon model appears to be sufficient for generating oscillations in intracranial pressure measurements as well as for causing an impact on cerebral hemodynamic conditions and valuable for studying the effects of mechanical damage to the brain tissue ( 43 ).…”
Section: Modelsmentioning
confidence: 99%